Impedance and Interface Properties of Al/Methyl-Red/p-InP Solar Cell - Ömer Güllü (International Journal of Photoenergy)
An Al/methyl-red/p-InP solar cell was fabricated via solution-processing method and was characterized by using current-voltage (I-V) and capacitance-voltage-frequency (C-V-f) measurements at room temperature. From dark I-V characteristics, the values of ideality factor and barrier height of the device were calculated as 1.11 eV and 2.02, respectively. It has been seen that the device exhibited a good photovoltaic behavior with a maximum open circuit voltage Voc of 0.38 V and short-circuit current Isc of 2.8 nA under only 200 lx light intensity. The barrier height and acceptor carrier concentration values for the Al/methyl-red/p-InP devices were extracted as 1.27 eV and 3.46×1017 cm-3 from linear region of its C-2-V characteristics, respectively. The difference between Φb (I-V) and Φb (C-V) for Al/methyl-red/p-InP device was attributed the different nature of the I-V and C-V measurements. Also, the energy distribution curves of the interface states and their time constants were obtained from the experimental conductance properties of the Al/methyl-red/p-InP structure at room temperature. The interface state densities and their relaxation times of the device have ranged from 2.96×1012 cm-2eV-1 and 4.96×10-6 s at (1.11-Ev) eV to 5.19×1012 cm-2 eV-1 and 9.39×10-6 s at (0.79-Ev) eV, respectively. It was seen that both the interface state density and the relaxation time of the interface states have decreased with bias voltage from experimental results.